Understanding Patient Needs for Quality Health Services at Primary Healthcare After the Covid-19 Pandemic - Sudirman Sudirman; Saiful Ambodale; Niluh Desy Purnama Sari; Subardin. AB; Ni Kadek Armini (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: The demands of patient needs for the quality of health services at the Bulili primary Healthcare have continued to increase since the onset of the Covid-19 pandemic where the number of patient visits has decreased significantly. Return visits by patients at primary Healthcare are an indication of low public confidence in the quality of health services provided. This study aims to evaluate the quality of health services at the Bulili Primary Healthcare by focusing on patient assessment after the COVID-19 pandemic. Methods: This study using a quantitative descriptive design influenced by Donabedian's quality framework, the study examined variables such as effectiveness, efficiency, patient-centeredness, timeliness, safety, and equity. Data were collected from 44 patients through structured interviews and analyzed using Anova to explore the variability and significance of service quality dimensions. Results: The results showed a significant difference (P-Value: 0.008) in patient needs in the aspect of health service quality at the Bulili Primary Healthcare. Service effectiveness and efficiency, timeliness of service, patient-centered care, fairness or equity in care vary widely and have the greatest influence on quality needs in patients. Punctuality, and postulate or equity in service delivery, require urgent improvements to meet the need for quality of care in patients. This study also identifies potential areas for further research in the development and implementation of strategies to improve service quality in primary healthcare that can be widely adapted. Conclusion: The conclusion is the need for a responsive and patient-centered approach in the setting of equity or equity, timeliness, effectiveness and efficiency, and patient-centered care.